Preparation method of bimetallic nanoparticles and application of bimetallic nanoparticles in lithium-sulfur battery

Co3ZnC nanoparticle carbon derivatives were prepared through Joule thermal rapid sintering technology, which solved the problems of low sulfur conductivity and lithium polysulfide dissolution in lithium sulfur batteries, and achieved improvement in battery performance.

CN119858920AActive Publication Date: 2025-04-22HEFEI UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510062457.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-22
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The low conductivity of sulfur in lithium-sulfur batteries and the dissolution of lithium polysulfides lead to unstable battery performance. The existing catalyst preparation methods are long and have high energy consumption, resulting in large particle size, poor dispersion and low activity.

Method used

Co3ZnC nanoparticle carbon derivatives were prepared by Joule thermal rapid sintering technology. Through the porous structure of the ZIF-8@ZIF-67 precursor and the active site of Co3ZnC, catalytic activity was improved and the dissolution of polysulfides was inhibited.

Benefits of technology

The high conductivity and excellent catalytic performance of Co3ZnC nanoparticle carbon derivatives in lithium sulfur batteries are achieved, the long cycle stability and rate performance of the battery are improved, and the problems of sulfur positive electrode capacity attenuation and polysulfide shuttle effect are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119858920A_ABST
    Figure CN119858920A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of bimetallic nanoparticles and application of the bimetallic nanoparticles in a lithium-sulfur battery. The preparation method of the bimetallic nanoparticles comprises the following steps: preparing a ZIF-8 seed, preparing ZIF-8-ZIF-67 powder and obtaining a Co3ZnC nanoparticle carbon derivative by using a Joule heat rapid sintering technology. The Co3ZnC nano-particle carbon derivative prepared by the invention has a stable framework provided by a ZIF-8 and ZIF-67 precursor, and can inhibit the diffusion of polysulfide; catalytic conversion of polysulfide is accelerated by active sites with Co and ZnC; therefore, high conductivity, excellent catalytic performance and strong chemical adsorption capacity to polysulfide are realized. The Co3ZnC nano-particle carbon derivative has a relatively good prospect when being applied to a lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of inorganic functional material synthesis, and specifically relates to a method for preparing bimetallic nanoparticles and application of the bimetallic nanoparticles in lithium-sulfur batteries. Background Art

[0002] Lithium-sulfur batteries (Li-S batteries) have become an important research direction for the next generation of battery technology due to their high theoretical energy density (about 500Wh / kg). Compared with traditional lithium-ion batteries, lithium-sulfur batteries have significant advantages, especially in terms of high energy density and low cost, which makes them have wide application potential in electric vehicles, portable electronic devices and other fields. However, lithium-sulfur batteries still face multiple technical challenges in practical applications, mainly including low conductivity of sulfur, dissolution of lithium polysulfides and poor battery cycle performance. First, sulfur, as an active substance in the battery, has low conductivity, which limits its effective use in the battery. Secondly, during the charge and discharge process, sulfur will be converted into soluble lithium polysulfides (LiS), which may dissolve in the electrolyte, resulting in the attenuation of battery capacity, further affecting the efficiency and stability of the battery. Therefore, how to improve the conductivity of sulfur and inhibit the dissolution of lithium polysulfides has become the key to improving the performance of lithium-sulfur batteries. In order to solve these problems, researchers have proposed a variety of strategies, one of which is to introduce catalysts to improve the electrochemical performance of lithium-sulfur batteries.

[0003] Chinese patent CN118978146A (publication date: November 19, 2024) discloses a Co 0.5 Ni 0.5 Preparation method of Te2 nanoparticle / three-dimensional carbon sheet composite material and its application in lithium-sulfur batteries, in which nanoparticles are evenly distributed on the surface of carbon sheets, chemically adsorb and catalyze the kinetic transformation of polysulfide ions; at the same time, the three-dimensional carbon sheet with a cross-linked network structure provides a continuous electron transmission channel to ensure the rapid transmission of charge. The synthesis method provided in this application is simple, universal and reproducible; using it for lithium-sulfur battery separator coating materials can effectively improve the battery specific capacity and cycle stability.

[0004] Chinese patent CN115832312A (publication date: March 21, 2023) discloses a method for preparing a lithium-sulfur battery catalyst material, which is used to prepare a lithium-sulfur battery catalyst material in which atomically dispersed Ni Co bimetallic tandem sites are coordinated with nitrogen and embedded in porous carbon, comprising the following steps: step S1, dissolving Zn(NO3)2·6H2O, Co(NO3)2·6H2O and Ni(NO3)2·6H2O in methanol to form a mixed solution, adding 2-methylimidazole and methanol to the mixed solution, stirring and aging, and then filtering and collecting the precipitate. After washing and vacuum drying the precipitate, ZnCoNi ZIF is obtained; step S2, ZnCoNi ZIF is placed in a tubular furnace and heated to obtain a pyrolysis product. After the pyrolysis product is soaked, the metal particles on the surface are selectively removed, and then vacuum dried to obtain a lithium-sulfur battery catalyst material CoNi NC.

[0005] Chinese patent CN112670669A (publication date: April 16, 2021) discloses the application of a nitrogen-doped carbon-coated Co and / or Co3ZnC composite material in the preparation of lithium-sulfur battery separators. First, PluronicF127 is dissolved in water, and a carbon source dicyandiamide is added, followed by a divalent cobalt salt and a divalent zinc salt. After further stirring, the water is evaporated to obtain a solid composite, and then high-temperature carbonization is performed under the protection of N2 gas. In this process, dicyandiamide is carbonized to obtain N-doped carbon, and the reducing substances such as carbon monoxide, carbon dioxide, nitric oxide, and carbon produced by dicyandiamide during the carbonization process can reduce and carbonize cobalt and zinc to obtain Co or Co3ZnC, and the target product is obtained after the reaction is completed. The N-doped carbon-coated Co and / or Co3ZnC composite material is used as a separator modification material and coated on a commercial separator using a doctor blade method. It can be effectively used in lithium-sulfur batteries to improve the electrochemical performance of lithium-sulfur batteries.

[0006] After searching and analyzing, it is found that the bimetallic nanoparticles used as catalysts to improve the performance of lithium-sulfur batteries need to be further developed; most positive electrode materials currently contain only a single metal, and the catalytic efficiency is limited; and the traditional catalyst preparation method usually takes a long time and high energy consumption, which will lead to larger catalyst particle size, poor dispersion, and may reduce the activity of the catalyst. In order to solve the above problems, it is urgent to invent a new synthetic bimetallic nanoparticle as a lithium-sulfur battery catalyst. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a method for preparing bimetallic nanoparticles and application of the bimetallic nanoparticles in lithium-sulfur batteries.

[0008] A method for preparing bimetallic nanoparticles comprises the following steps:

[0009] Step S1: dispensing ZIF-8 seeds according to the ratio;

[0010] Step S2: preparing a ZIF-8@ZIF-67 solution according to a ratio to obtain a ZIF-8@ZIF-67 powder;

[0011] Step S3: Use Joule heat rapid sintering technology to sinter ZIF-8@ZIF-67 powder to obtain Co3ZnC nanoparticle carbon derivatives.

[0012] Furthermore, the step S1 includes the following steps:

[0013] Step S101: adding 2-methylimidazole to distilled water and performing ultrasonic dispersion to obtain solution A;

[0014] Step S102: adding zinc acetate dihydrate into distilled water and performing ultrasonic dispersion to obtain solution B;

[0015] Step S103: adding solution B to the stirring solution A, stirring for 10 to 30 seconds, and standing at room temperature for 24 to 36 hours to obtain a mixed solution A;

[0016] Step S104: taking out the supernatant from the mixed solution A, centrifuging the remaining precipitate of the mixed solution A with distilled water in a centrifuge at 8000-10000 rpm / min for 5-10 min, repeating the washing 2-3 times, and then washing with anhydrous ethanol 1-2 times to obtain a precipitate A;

[0017] Step S105: drying the obtained precipitate A in an oven at 70° C. to 80° C. for 8 to 12 hours to obtain ZIF-8 seeds.

[0018] Furthermore, the step S2 includes the following steps:

[0019] Step S201: adding ZIF-8 seeds into distilled water for ultrasonic dispersion to obtain a ZIF-8 suspension;

[0020] Step S202: adding 2-methylimidazole to distilled water for ultrasonic dispersion to obtain solution C;

[0021] Step S203: adding cobalt acetate tetrahydrate into distilled water for ultrasonic dispersion to obtain solution D;

[0022] Step S204: adding solution D to the ZIF-8 suspension for ultrasonic dispersion to obtain a purple suspension E;

[0023] Step S205: adding the suspension E to the stirring solution C, stirring for 10 to 30 seconds, and standing at room temperature for 24 to 36 hours to obtain a mixed solution B;

[0024] Step S206: taking out the supernatant in the mixed solution B, centrifuging the remaining precipitate of the mixed solution B with distilled water in a centrifuge at 8000-10000 rpm / min for 5-10 min, repeating the washing 2-3 times, and then washing with anhydrous ethanol 1-2 times to obtain a precipitate B;

[0025] Step S207: drying the precipitate B in an oven at 70° C. to 80° C. for 8 to 12 hours to obtain ZIF-8@ZIF-67 powder.

[0026] Furthermore, the step S3 includes the following steps:

[0027] Step S301: placing the obtained ZIF-8@ZIF-67 powder into a Joule heat rapid sintering device;

[0028] Step S302: Sintering at 700° C. to 900° C. for 20 seconds to 40 seconds in an argon environment to obtain a Co3ZnC nanoparticle carbon derivative.

[0029] Further, the content of 2-methylimidazole in every 5 ml of solution A is 1g to 2g; the content of zinc acetate dihydrate in every 5 ml of solution B is 0.15g to 0.45g; the content of 2-methylimidazole in every 5 ml of solution C is 0.5g to 1g; and the content of cobalt acetate tetrahydrate in every 5 ml of solution D is 0.1g to 0.3g.

[0030] Furthermore, the diameter of the Co3ZnC nanoparticle carbon derivative is 600nm to 1500nm.

[0031] A method for preparing a positive electrode sheet of a Co3ZnC nanoparticle carbon derivative comprises the following steps:

[0032] Step 1: Grind and mix the Co3ZnC nanoparticle carbon derivative powder and sublimated sulfur powder to obtain mixed powder A;

[0033] Step 2: Place the mixed powder A into a sealed titanium tube, keep it in a tube furnace at 155°C for 12h to 24h, and then cool it to room temperature in the furnace;

[0034] Step 3: Grind the cooled mixed powder A fully, put it into a tube furnace, keep it at 200°C for 1h to 2h under argon atmosphere, and then cool it to room temperature with the furnace to obtain Co3ZnC nanoparticle carbon derivative loaded with sulfur;

[0035] Step 4: Adding the Co3ZnC nanoparticle carbon derivative loaded with sulfur, a conductive agent and a binder into a ball mill;

[0036] Step 5: Add solvent E to the ball mill, grind, and evenly mix to form a fluid electrode slurry;

[0037] Step 6: Use a scraper to evenly scrape the electrode slurry on the surface of the aluminum foil, and then place the aluminum foil in a forced air drying oven at 70°C to 80°C and dry it for 8 to 12 hours. After it is completely dried, the Co3ZnC nanoparticle carbon derivative positive electrode sheet is obtained.

[0038] Furthermore, the mass ratio of the Co3ZnC nanoparticle carbon derivative powder to the sublimated sulfur powder is 3:7;

[0039] Furthermore, the mass ratio of the Co3ZnC nanoparticle carbon derivative, the conductive agent and the binder after loading sulfur is 7:2:1.

[0040] Furthermore, the conductive agent includes Ketjen black; the binder includes polyvinylidene fluoride; and the solvent E includes N-methylpyrrolidone.

[0041] The invention discloses an application of a Co3ZnC nanoparticle carbon derivative positive electrode sheet in the preparation of a lithium-sulfur battery.

[0042] Compared with the prior art, the advantages and effects of the present invention are as follows:

[0043] 1. The present invention can obtain Co3ZnC nanoparticle carbon derivatives with a porous structure in a short time by using Joule heat rapid sintering technology, which can effectively avoid the problems of large particle size and poor dispersibility, thereby improving its catalytic activity; and make the Co3ZnC nanoparticle carbon derivatives show excellent long-cycle stability and rate performance in lithium-sulfur batteries.

[0044] 2. The present invention solves the problems of sulfur positive electrode capacity attenuation and polysulfide shuttle effect in lithium-sulfur batteries by using Co3ZnC nanoparticle carbon derivatives to prepare lithium-sulfur batteries.

[0045] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application so that it can be implemented in accordance with the contents of the specification, and to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the following is a detailed description of the preferred embodiments of the present application in conjunction with the accompanying drawings as follows.

[0046] Based on the detailed description of the specific embodiments of the present application in combination with the accompanying drawings below, those skilled in the art will become more aware of the above and other objects, advantages and features of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can also be obtained based on these drawings without creative work. In all drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale.

[0048] in:

[0049] Figure 1 This is a flow chart of the method for preparing bimetallic nanoparticles of the present application;

[0050] Figure 2 TEM image of the Co3ZnC nanoparticle carbon derivative described in this application;

[0051] Figure 2 (a) is a TEM image of the Co3ZnC nanoparticle carbon derivative described in this application with a scale of 500 nm;

[0052] Figure 2 (b) is a TEM image of the Co3ZnC nanoparticle carbon derivative described in the present application with a scale of 20 nm;

[0053] Figure 2 (c) is a TEM image of the Co3ZnC nanoparticle carbon derivative described in this application with a scale of 10 nm;

[0054] Figure 3 is the XRD image of the secondary battery described in this application;

[0055] Figure 4 Different current density cycle diagrams and rate images of the secondary battery described in this application;

[0056] Figure 4 (a) is a cycle diagram of the secondary batteries of the control group and experimental group 3 described in this application under the condition of 0.5C current density;

[0057] Figure 4 (b) is a cycle diagram of the secondary battery of the control group and experimental group 3 described in the present application under 1C current density conditions;

[0058] Figure 4 (c) is a cycle diagram of the secondary batteries of the control group and experimental group 3 described in the present application under 2C current density conditions;

[0059] Figure 4 (d) is a rate image of the secondary batteries of the control group and experimental group 3 described in the present application at a cut-off voltage of 2.8V. DETAILED DESCRIPTION

[0060] To make the purpose, technical scheme and advantages of the embodiment of the present application clearer, the technical scheme in the embodiment of the present application will be clearly and completely described below in conjunction with the accompanying drawings in the embodiment of the present application. Obviously, the described embodiment is a part of the embodiment of the present application, rather than all of the embodiments. In the following description, specific details such as specific configuration and components are provided only to help fully understand the embodiments of the present application. Therefore, it should be clear to those skilled in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present application. In addition, for clarity and brevity, the description of known functions and structures is omitted in the embodiment.

[0061] It should be understood that the references to "one embodiment" or "this embodiment" throughout the specification mean that the specific features, structures, or characteristics associated with the embodiment are included in at least one embodiment of the present application. Therefore, the references to "one embodiment" or "this embodiment" appearing throughout the specification do not necessarily refer to the same embodiment. In addition, these specific features, structures, or characteristics may be combined in any suitable manner in one or more embodiments.

[0062] In addition, the present application may repeat reference numerals and / or letters in different examples. This repetition is for the purpose of simplicity and clarity, and does not in itself indicate the relationship between the various embodiments and / or settings discussed.

[0063] The term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, B exists alone, and A and B exist at the same time. The term " / and" in this article describes another type of association object relationship, indicating that there can be two relationships. For example, A / and B can mean: A exists alone, and A and B exist alone. In addition, the character " / " in this article generally indicates that the previous and next associated objects are in an "or" relationship.

[0064] The term "at least one" in this article is merely a description of the association relationship of associated objects, indicating that there may be three relationships. For example, at least one of A and B can mean: A exists alone, A and B exist at the same time, and B exists alone.

[0065] It should also be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusions.

[0066] Example 1

[0067] This embodiment is a method for preparing bimetallic nanoparticles.

[0068] Please refer to Figure 1 , a flow chart of the method for preparing bimetallic nanoparticles of the present application. A method for preparing bimetallic nanoparticles comprises the following steps:

[0069] Step S1: dispensing ZIF-8 seeds according to the ratio;

[0070] Step S2: preparing a ZIF-8@ZIF-67 solution according to a ratio to obtain a ZIF-8@ZIF-67 powder;

[0071] Step S3: Use Joule heat rapid sintering technology to sinter ZIF-8@ZIF-67 powder to obtain Co3ZnC nanoparticle carbon derivatives.

[0072] Furthermore, the step S1 includes the following steps:

[0073] Step S101: adding 2-methylimidazole to distilled water and performing ultrasonic dispersion to obtain solution A;

[0074] Step S102: adding zinc acetate dihydrate into distilled water and performing ultrasonic dispersion to obtain solution B;

[0075] Step S103: adding solution B to solution A, stirring for 10 to 30 seconds, and standing at room temperature for 24 to 36 hours to obtain a mixed solution A;

[0076] Step S104: taking out the supernatant from the mixed solution A, centrifuging the remaining precipitate of the mixed solution A with distilled water in a centrifuge at 8000-10000 rpm / min for 5-10 min, repeating the washing 2-3 times, and then washing with anhydrous ethanol 1-2 times to obtain a precipitate A;

[0077] Step S105: drying the obtained precipitate A in an oven at 70° C. to 80° C. for 8 to 12 hours to obtain ZIF-8 seeds.

[0078] Furthermore, the step S2 includes the following steps:

[0079] Step S201: adding ZIF-8 seeds into distilled water for ultrasonic dispersion to obtain a ZIF-8 suspension;

[0080] Step S202: adding 2-methylimidazole to distilled water for ultrasonic dispersion to obtain solution C;

[0081] Step S203: adding cobalt acetate tetrahydrate into distilled water for ultrasonic dispersion to obtain solution D;

[0082] Step S204: adding solution D to the ZIF-8 suspension for ultrasonic dispersion to obtain a purple suspension E;

[0083] Step S205: adding the suspension E to the solution C, stirring for 10 to 30 seconds, and standing at room temperature for 24 to 36 hours to obtain a mixed solution B;

[0084] Step S206: taking out the supernatant in the mixed solution B, centrifuging the remaining precipitate of the mixed solution B with distilled water in a centrifuge at 8000-10000 rpm / min for 5-10 min, repeating the washing 2-3 times, and then washing with anhydrous ethanol 1-2 times to obtain a precipitate B;

[0085] Step S207: drying the precipitate B in an oven at 70° C. to 80° C. for 8 to 12 hours to obtain ZIF-8@ZIF-67 powder.

[0086] Furthermore, the step S3 includes the following steps:

[0087] Step S301: placing the obtained ZIF-8@ZIF-67 powder into a Joule heat rapid sintering device;

[0088] Step S302: Sintering at 700° C. to 900° C. for 20 seconds to 40 seconds in an argon environment to obtain a Co3ZnC nanoparticle carbon derivative.

[0089] Further, the content of 2-methylimidazole in every 5 ml of solution A is 1g to 2g; the content of zinc acetate dihydrate in every 5 ml of solution B is 0.15g to 0.45g; the content of 2-methylimidazole in every 5 ml of solution C is 0.5g to 1g; and the content of cobalt acetate tetrahydrate in every 5 ml of solution D is 0.1g to 0.3g.

[0090] Please refer to Figure 2 , is the TEM image of the Co3ZnC nanoparticle carbon derivative described in the present application; further, the diameter of the Co3ZnC nanoparticle carbon derivative is 600nm to 1500nm.

[0091] Technical effect of this embodiment: Traditional catalyst synthesis methods often require a long time and high-temperature treatment, resulting in larger catalyst particle size and poor dispersibility, thus affecting its activity. The ZIF-8@ZIF-67 precursor is carbonized using Joule heat sintering technology to quickly synthesize a catalyst containing bimetallic alloy Co3ZnC nanoparticles. During the sintering process, the ZIF-8@ZIF-67 precursor provides a stable skeleton to inhibit the diffusion of polysulfides, while the active sites of Co3ZnC accelerate the catalytic conversion of polysulfides. The final formed Co3ZnC has high conductivity, excellent catalytic performance, and strong chemical adsorption capacity for polysulfides.

[0092] Example 2

[0093] Based on Example 1, a method for preparing a Co3ZnC nanoparticle carbon derivative positive electrode sheet.

[0094] A method for preparing a positive electrode sheet of a Co3ZnC nanoparticle carbon derivative comprises the following steps:

[0095] Step 1: Grind and mix the Co3ZnC nanoparticle carbon derivative powder and sublimated sulfur powder to obtain mixed powder A;

[0096] Step 2: Place the mixed powder A into a sealed titanium tube, keep it in a tube furnace at 155°C for 12h to 24h, and then cool it to room temperature in the furnace;

[0097] Step 3: Grind the cooled mixed powder A fully, put it into a tube furnace, keep it at 200°C for 1h to 2h under argon atmosphere, and then cool it to room temperature with the furnace to obtain Co3ZnC nanoparticle carbon derivative loaded with sulfur;

[0098] Step 4: Adding the Co3ZnC nanoparticle carbon derivative loaded with sulfur, a conductive agent and a binder into a ball mill;

[0099] Step 5: Add solvent E to the ball mill, grind, and evenly mix to form a fluid electrode slurry;

[0100] Step 6: Use a scraper to evenly scrape the electrode slurry on the surface of the aluminum foil, and then place the aluminum foil in a forced air drying oven at 70°C to 80°C and dry it for 8 to 12 hours. After it is completely dried, the Co3ZnC nanoparticle carbon derivative positive electrode sheet is obtained.

[0101] Furthermore, the mass ratio of the Co3ZnC nanoparticle carbon derivative powder to the sublimated sulfur powder is 3:7;

[0102] Furthermore, the mass ratio of the Co3ZnC nanoparticle carbon derivative, the conductive agent and the binder after loading sulfur is 7:2:1.

[0103] Furthermore, the conductive agent includes Ketjen black; the binder includes polyvinylidene fluoride; and the solvent E includes N-methylpyrrolidone.

[0104] The technical effect of this embodiment is as follows: by loading sulfur element on Co3ZnC nanoparticle carbon derivatives to prepare positive electrode sheets, the conductivity of sulfur can be improved and the dissolution of lithium polysulfide can be inhibited, thereby improving the performance of lithium-sulfur batteries.

[0105] Example 3

[0106] Based on Example 2, this example is a method for preparing a lithium-sulfur battery using a Co3ZnC nanoparticle carbon derivative positive electrode plate.

[0107] A method for preparing a lithium-sulfur battery using a positive electrode sheet of a Co3ZnC nanoparticle carbon derivative comprises the following steps:

[0108] Step SS1: compact the Co3ZnC nanoparticle carbon derivative positive electrode sheet using a roller press, and cut the Co3ZnC nanoparticle carbon derivative positive electrode sheet into positive electrode discs with a diameter of 14 mm using a punching machine, and put the cut positive electrode discs into a 60° C. vacuum drying oven for 12 h for later use;

[0109] Step SS2: At room temperature, 1 mol / L LITFSI was added to a solution containing 2% LiNO3 in a volume ratio of 1:1 of ethylene glycol dimethyl ether and 1,3-dioxolane, and the mixture was mixed thoroughly and allowed to stand for 24 h to obtain an electrolyte.

[0110] Step SS3: punching the polyethylene diaphragm into a disc with a diameter of 16 mm, transferring it to a vacuum drying oven at 55° C., and vacuum drying it for 24 h to obtain the diaphragm;

[0111] Step SS4: In a glove box with water and oxygen content less than 0.1 ppm, a lithium sheet is used as a counter electrode and is assembled with the electrolyte obtained in step S502, the positive electrode disc, and the separator into a secondary battery.

[0112] The technical effect of this embodiment is as follows: In a lithium-sulfur battery, the use of Co3ZnC nanoparticle carbon derivative positive electrode sheet can not only promote the reduction reaction of lithium polysulfide, but also improve the overall performance of the battery by providing more active sites and improving electrical conductivity.

[0113] Example 4

[0114] Based on the above-mentioned embodiments 1-3, this embodiment mainly introduces the effect verification of a lithium-sulfur battery using a Co3ZnC nanoparticle carbon derivative positive electrode plate.

[0115] In the process of preparing lithium-sulfur batteries, other conditions were controlled to remain consistent, and the sintering temperature and duration in step S302 were changed to obtain different secondary batteries, which were named control group, experimental group 1, experimental group 2, experimental group 3, experimental group 4, and experimental group 5 respectively; their corresponding sintering temperatures and sintering times are shown in Table 1 below.

[0116] Table 1 Comparison table of sintering temperature and sintering time

[0117]

[0118] The Arbin BT2000 test system was used to test the secondary batteries of the control group and the experimental group. The charge and discharge voltage range was 1.7 to 2.8 V. The batteries were cycled 500 times (25°C) at 0.5C, 1C and 2C to obtain the cycle performance. The test results are shown in Table 2.

[0119] Table 2 Test results of Arbin BT2000 test system for secondary batteries

[0120]

[0121] Please refer to Figure 3 , is the XRD image of the secondary battery described in this application; please refer to Figure 4 , which are the different current density cycle diagrams and rate images of the secondary battery described in this application. Figure 3-4 As can be seen from Table 2, after 500 cycles, experimental groups 1 to 5 can maintain a high specific capacity, especially experimental group 3, which can maintain a specific capacity of 556.51 mAh / g after 500 cycles at a current density of 2C, while the control group cannot cycle 500 cycles at a current density of 2C. And the overall capacity is not as high as that of the battery containing CoZnC.

[0122] Technical effect of this embodiment: Co ZnC is prepared by high-temperature sintering of the double-layer structure of the ZIF-8@ZIF-67 precursor, and the double-layer porous structure of the ZIF-8@ZIF-67 precursor and the high catalytic activity of Co ZnC are used to achieve structural and functional optimization. During the sintering process, the ZIF-8@ZIF-67 precursor provides a stable skeleton to inhibit the diffusion of polysulfides, while the active sites of CoZnC accelerate the catalytic conversion of polysulfides. The final CoZnC has high conductivity, excellent catalytic performance, and strong chemical adsorption capacity for polysulfides.

[0123] In summary, the present invention provides a method for preparing bimetallic nanoparticles and their application in lithium-sulfur batteries. By using Joule heat rapid sintering technology, Co3ZnC nanoparticle carbon derivatives with a porous structure can be obtained in a short time, which can effectively avoid the problems of large particle size and poor dispersibility, thereby improving their catalytic activity; Co3ZnC nanoparticle carbon derivatives show excellent long-cycle stability and rate performance in lithium-sulfur batteries. By using Co3ZnC nanoparticle carbon derivatives to prepare lithium-sulfur batteries, the problems of sulfur positive electrode capacity attenuation and polysulfide shuttling effect in lithium-sulfur batteries are solved; the invention is innovative.

[0124] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing bimetallic nanoparticles, characterized in that: The following steps are involved: Step S1: dispensing ZIF-8 seeds according to the ratio; Step S2: preparing a ZIF-8@ZIF-67 solution according to a ratio to obtain a ZIF-8@ZIF-67 powder; Step S3: Use Joule heat rapid sintering technology to sinter ZIF-8@ZIF-67 powder to obtain Co3ZnC nanoparticle carbon derivatives.

2. The method for preparing bimetallic nanoparticles according to claim 1, characterized in that: The step S1 comprises the following steps: Step S101: adding 2-methylimidazole to distilled water and performing ultrasonic dispersion to obtain solution A; Step S102: adding zinc acetate dihydrate into distilled water and performing ultrasonic dispersion to obtain solution B; Step S103: adding solution B to solution A, stirring for 10 to 30 seconds, and standing at room temperature for 24 to 36 hours to obtain a mixed solution A; Step S104: taking out the supernatant from the mixed solution A, centrifuging the remaining precipitate of the mixed solution A with distilled water in a centrifuge at 8000-10000 rpm / min for 5-10 min, repeating the washing 2-3 times, and then washing with anhydrous ethanol 1-2 times to obtain a precipitate A; Step S105: drying the obtained precipitate A in an oven at 70° C. to 80° C. for 8 to 12 hours to obtain ZIF-8 seeds.

3. The method for preparing bimetallic nanoparticles according to claim 2, characterized in that: The step S2 comprises the following steps: Step S201: adding ZIF-8 seeds into distilled water for ultrasonic dispersion to obtain a ZIF-8 suspension; Step S202: adding 2-methylimidazole to distilled water and dispersing by ultrasonication to obtain solution C; Step S203: adding cobalt acetate tetrahydrate into distilled water for ultrasonic dispersion to obtain solution D; Step S204: adding solution D to the ZIF-8 suspension for ultrasonic dispersion to obtain a purple suspension E; Step S205: adding the suspension E to the solution C, stirring for 10 to 30 seconds, and standing at room temperature for 24 to 36 hours to obtain a mixed solution B; Step S206: taking out the supernatant in the mixed solution B, centrifuging the remaining precipitate of the mixed solution B with distilled water in a centrifuge at 8000-10000 rpm / min for 5-10 min, repeating the washing 2-3 times, and then washing with anhydrous ethanol 1-2 times to obtain a precipitate B; Step S207: drying the precipitate B in an oven at 70° C. to 80° C. for 8 to 12 hours to obtain ZIF-8@ZIF-67 powder.

4. The method for preparing bimetallic nanoparticles according to claim 3, characterized in that: The step S3 comprises the following steps: Step S301: placing the obtained ZIF-8@ZIF-67 powder into a Joule heat rapid sintering device; Step S302: Sintering at 700° C. to 900° C. for 20 seconds to 40 seconds in an argon environment to obtain a Co3ZnC nanoparticle carbon derivative.

5. The method for preparing bimetallic nanoparticles according to claim 4, characterized in that: The content of 2-methylimidazole in each 5 ml of solution A is 1 g to 2 g; The content of zinc acetate dihydrate in each 5 ml of solution B is 0.15 g to 0.45 g; The content of 2-methylimidazole added in every 5 ml of solution C is 0.5 g to 1 g; The content of cobalt acetate tetrahydrate in each 5 ml of solution D is 0.1 g to 0.3 g.

6. The method for preparing bimetallic nanoparticles according to claim 5, characterized in that: The diameter of the Co3ZnC nanoparticle carbon derivative is 600nm-1500nm.

7. A method for preparing a positive electrode sheet of a Co3ZnC nanoparticle carbon derivative using the Co3ZnC nanoparticle carbon derivative obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Grind and mix Co3ZnC nanoparticle carbon derivative powder and sublimated sulfur powder to obtain mixed powder A; Step 2: Place the mixed powder A into a sealed titanium tube, keep it in a tube furnace at 155°C for 12h to 24h, and then cool it to room temperature in the furnace; Step 3: Grind the cooled mixed powder A fully, put it into a tube furnace, keep it at 200°C for 1h to 2h under argon atmosphere, and then cool it to room temperature with the furnace to obtain Co3ZnC nanoparticle carbon derivative loaded with sulfur; Step 4: Adding the Co3ZnC nanoparticle carbon derivative loaded with sulfur, a conductive agent and a binder into a ball mill; Step 5: Add solvent E to the ball mill, grind, and evenly mix to form a fluid electrode slurry; Step 6: Use a scraper to evenly scrape the electrode slurry on the surface of the aluminum foil, and then place the aluminum foil in a forced air drying oven at 70°C to 80°C and dry it for 8 to 12 hours. After it is completely dried, the Co3ZnC nanoparticle carbon derivative positive electrode sheet is obtained.

8. The method for preparing the Co3ZnC nanoparticle carbon derivative positive electrode sheet according to claim 7, characterized in that: The mass ratio of the Co3ZnC nanoparticle carbon derivative powder to the sublimated sulfur powder is 2.5-3.5:6.5-7.5; The mass ratio of the Co3ZnC nanoparticle carbon derivative, the conductive agent and the binder after loading sulfur is 7:2:

1.

9. The method for preparing the Co3ZnC nanoparticle carbon derivative positive electrode sheet according to claim 7, characterized in that: The conductive agent includes Ketjen black; The binder includes polyvinylidene fluoride; The solvent E includes N-methylpyrrolidone.

10. Use of the Co3ZnC nanoparticle carbon derivative positive electrode sheet obtained by the preparation method according to claim 8 or 9 in the preparation of lithium-sulfur batteries.

Citation Information

Patent Citations

  • Dodecahedral porous Co3ZnC / C composite material preparation method and use of dodecahedral porous Co3ZnC / C composite material in lithium ion battery

    CN106058215A

  • Preparation method of 3D-ZIF8@zif67 for lithium-sulfur battery cathode material

    CN110611099A

  • Zinc-cobalt sulfide / carbon nano negative electrode material and preparation method thereof

    CN111293300A

  • Battery positive electrode material and method for rapidly synthesizing battery positive electrode material

    CN113247962A

  • CoSe2 / NC-CNT / S lithium-sulfur battery negative electrode material and preparation method thereof

    CN114709399A